2016
DOI: 10.1155/2016/9746313
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Research on Diffuse Axonal Injury after Traumatic Brain Injury

Abstract: The current work reviews the concept, pathological mechanism, and process of diagnosing of DAI. The pathological mechanism underlying DAI is complicated, including axonal breakage caused by axonal retraction balls, discontinued protein transport along the axonal axis, calcium influx, and calpain-mediated hydrolysis of structural protein, degradation of axonal cytoskeleton network, the changes of transport proteins such as amyloid precursor protein, and changes of glia cells. Based on the above pathological mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 46 publications
1
86
0
1
Order By: Relevance
“…These two loading conditions are cases of clinical interest. A constant pressure on an axon is representative of injuries [1], [3] and plaques in demyelinating diseases, acting as conduction block for action potentials of neighbouring 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 P e e r R e v i e w O n l y 11 axons inhibiting the myelinisation process. Instead, elongation tests might explain the relatively long time period needed for spontaneous membrane repair after fast strain [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These two loading conditions are cases of clinical interest. A constant pressure on an axon is representative of injuries [1], [3] and plaques in demyelinating diseases, acting as conduction block for action potentials of neighbouring 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 P e e r R e v i e w O n l y 11 axons inhibiting the myelinisation process. Instead, elongation tests might explain the relatively long time period needed for spontaneous membrane repair after fast strain [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this section, the fully coupled electro-mechanical model of Fig. 2 is applied to investigate different mechanical loading conditions directly using equations (1)(2)(3)(4), instead of as a simulated voltage-shift. Fig.…”
Section: B Mechanical Loading Cases Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Head injuries may result in traumatic brain injury (TBI), which is categorized as mild, moderate, and severe based on clinical symptoms and postmortem histology . The rapid acceleration‐deceleration of the head during TBI generates a diffusive form of microscale damage, such as diffuse axonal injury (DAI) and microvascular damage . However, microscale damage is difficult to detect with the current medical imaging technology due to hemorrhages, hematomas, and tissue lesions of the neighboring injured area .…”
Section: Introductionmentioning
confidence: 99%
“…The use of a 3D geometry with plastic material properties allows for the simulation and evaluation of strain and voltage distributions before and after the induced damage. The inclusion of 3D mechanically induced electrophysiological impairments is needed to enhance the understanding of electromechanical changes in neurotrauma evaluation and improve diagnosis, clinical treatment, and prognosis . This approach might prove crucial to study and understand the mechanics at play in neurophysiology, as observed experimentally in damaged nerve membranes of clinical cases such as multiple sclerosis …”
Section: Introductionmentioning
confidence: 99%